Spatial distribution patterns of protein and starch in wheat grain affect baking quality of bread and biscuit. (January 2018) - Zhou, Qin; Li, Xiangnan; Yang, Jianting; Zhou, Longjing; Cai, Jian; Wang, Xiao; Dai, Tingbo; Cao, Weixing; Jiang, Dong
Abstract: To evaluate the spatial distribution of chemicals and their contribution to processing quality, wheat grains were layered into nine fractions from the surface to the center layer. The content of total starch, amylose and amylopectin gradually increased from the surface layer to inner layer, while albumin, globulin and total protein decreased in this direction. Contents of gliadin, glutenin, high molecular weight glutenin subuints (HMW-GS) and glutenin macropolymers (GMP) increased from the surface layer, and peaked at the second or the third pearling layer, and then decreased till the center layer. The mean particle diameter of starch granules increased gradually from the surface to inner except at P9. Bread baking performance was the best for flour at the mid layers, while was the worst for flour from the surface layer, especially in terms of taste and texture. Biscuit making performance was the best at the center layers, while poorest at the surface layer. Highlights: Contents of starch and its composition increased inward from the surface layer. Content of protein and glutenin peaked at mid layers. Flour from the mid layers of the grain is most suitable for bread making. Flour from inner layers of the grain is most suitable for biscuit making.